PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI PADA MATERI JARINGAN TUMBUHAN UNTUK SMA - Rispianti, Yesi; Mulyati, Mulyati; Sari, Liza Yulia (STKIP PGRI Sumbar, 2013)
ABSTRAKIn achievement a learning objektives not only be affected by methods used the teacher. But also influenced by the teaching object used in the learning process. For that, we need some development teaching object from of student work sheet which aims to determine the validity and practicality student work sheet developed. This type of research is development with procedural models which aims to produce a product. The product was developed using a three stage from four-D models namely define, design, and develop. The study subject consisted of four validator and 20 students of class XI IPA3 from SMAN 4 Solok Selatan. Research data is the primary data by analizyng the validity and practicality of the developed student work sheet. From this study the object produced student work sheet tissues in plant for SMA class XI first semester. Student work sheet prodeced valid categorized by the validator to the value of 86,83% and categorized by teachers with the practical value of 87,64% and categorizedÂ by the students with the practical value of 87,52%. Thus, it can be concluded that the student work sheet development tissues in plant object for class XI SMA semester 1 had a valid and practical.